Development and validation of a pre-migration acculturation measure - Brown, Carrie M. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
An area that has been largely overlooked in the acculturation literature is acculturation that occurs before migration. Therefore, the goal of our study was to develop a measure of pre-migration acculturation that would assess relevant behaviors and anticipations developed in one’s country of origin before migration. Seventy-four university students who migrated to the United States of America at the age of 10 or older completed an online survey. The results revealed that both pre-migration anticipations and pre-migration behaviors demonstrated good Cronbach’s alphas, providing preliminary evidence of reliability. Pre-migration anticipations and pre-migration behaviors were moderately correlated, providing preliminary evidence of construct validity. Both pre-migration anticipations and pre-migration behaviors predicted post-migration acculturation to the United States (via a regression analysis), providing preliminary evidence of predictive validity.